Lazarus, His Friend - McIndoe, John (The expository times, 2005)
Presents a sermon by Reverend John McIndoe of Glasgow, Scotland for the March 13, 2005 mass. Overview of the story of Lazarus in the Gospel of John; Views of people on the story of Lazarus; Friendship between Jesus and Lazarus.